The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2013
DOI: 10.1371/journal.pone.0084539
|View full text |Cite
|
Sign up to set email alerts
|

Fungal Endophyte (Epichloë festucae) Alters the Nutrient Content of Festuca rubra Regardless of Water Availability

Abstract: Festuca rubra plants maintain associations with the vertically transmitted fungal endophyte Epichloë festucae. A high prevalence of infected host plants in semiarid grasslands suggests that this association could be mutualistic. We investigated if the Epichloë-endophyte affects the growth and nutrient content of F. rubra plants subjected to drought. Endophyte-infected (E+) and non-infected (E−) plants of two half-sib lines (PEN and RAB) were subjected to three water availability treatments. Shoot and root biom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
39
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 61 publications
(41 citation statements)
references
References 73 publications
2
39
0
Order By: Relevance
“…Fungal vertical inheritance is recognized as common mechanism of transfer across generations [39] and vertically transmitted fungal symbionts have been implicated in providing direct benefit to their host plant, such as in the case of improved drought tolerance of Festuca rubra given its fungal endophytre Epichloe¨festucae [40]. Furthermore, some studies have reported vertical transmission rates of greater than 90% for many fungal endosymbionts [41 ].…”
Section: Current Opinion In Microbiologymentioning
confidence: 99%
“…Fungal vertical inheritance is recognized as common mechanism of transfer across generations [39] and vertically transmitted fungal symbionts have been implicated in providing direct benefit to their host plant, such as in the case of improved drought tolerance of Festuca rubra given its fungal endophytre Epichloe¨festucae [40]. Furthermore, some studies have reported vertical transmission rates of greater than 90% for many fungal endosymbionts [41 ].…”
Section: Current Opinion In Microbiologymentioning
confidence: 99%
“…Several classes of endophyte metabolites with mammalian and insect toxicity, as well as invertebrate deterrent effects, have been characterized (Schardl and Phillips, 1997; Schardl et al, 2007, 2013). Epichloë infection can also elevate the tolerance of grasses to certain abiotic stresses (Arachevaleta et al, 1989; Malinowski and Belesky, 2000; Vázquez-de-Aldana et al, 2013). Given these attributes, these fungi are often prevalent in native grass habitats, but are also essential for persistence of forage in managed pastoral farming systems where insect pressure is high, as in New Zealand, Australia, and the Americas (Johnson et al, 2013a).…”
Section: Introductionmentioning
confidence: 99%
“…These effects could be a consequence of the substantial benefits that endophytic fungi may confer on hosting plants, such as drought tolerance (Hall et al 2014), resistance to herbivory and pathogens (Thom et al 2013;Romeralo et al 2015), enhanced nutrient uptake (Yang et al 2014), and increased competitive ability (Vázquez-de-Aldana et al 2013). However, this influence appears to be variable and clearly dependent on the species of endophyte, the host genotype and environmental conditions (Ahlholm et al 2002).…”
Section: Introductionmentioning
confidence: 99%